Community Based Peat Conservation - Arman Manalu (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2020)
Manalu A. 2020. Community based peat conservation. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands 9(1): 11-22.Peat forms naturally in swamp areas when dead plants rot and accumulate, which then decompresses and accumulates within hundreds to thousands of years. Peat can store 20 times more carbon than mineral soil. Indonesia's peatlands store about 46 Gt of carbon or around 8-14% of world peat carbon (Maltby and Immirizi, 1993). Peat has an important ecosystem that acts as a protector of the Earth's atmosphere from the greenhouse effect, ecological buffer, saves biodiversity and a place to live for various flora and fauna. Peat have the ability to resemble sponges which make them suitable as water catchment areas. The purpose of this study is to provide an overview of the importance of protecting and maintaining peatlands as protectors of the Earth's atmosphere, controlling global climate by involving the community. This research was conducted with qualitative descriptive methods taken from various literature and national media. The results showed that land degradation has occurred due to the extensive conversion of peatlands into plantations which in the process of causing environmental damage and peat ecosystems in various regions of Indonesia. For this reason, community-based peat conservation needs to be done so that sustainability is maintained and the community gets economic benefits from peatlands.